The Gaia spectrophotometric standard stars survey – IV. Results of the absolute photometry campaign. Issue 2 (24th November 2020) - Altavilla, G; Marinoni, S; Pancino, E; Galleti, S; Bellazzini, M; Sanna, N; Rainer, M; Tessicini, G; Carrasco, J M; Bragaglia, A; Schuster, W J; Cocozza, G; et al.
ABSTRACT: We present Johnson–Kron–Cousins BVRI photometry of 228 candidate spectrophotometric standard stars for the external (absolute) flux calibration of Gaia data. The data were gathered as part of a 10-yr observing campaign with the goal of building the external grid of flux standards for Gaia and we obtained absolute photometry, relative photometry for constancy monitoring, and spectrophotometry. Preliminary releases of the flux tables were used to calibrate the first two Gaia releases. This paper focuses on the imaging frames observed in good sky conditions (about 9100). The photometry will be used to validate the ground-based flux tables of the Gaia spectrophotometric standard stars and to correct the spectra obtained in non-perfectly photometric observing conditions for small zero-point variations. The absolute photometry presented here is tied to the Landolt standard stars system to ≃1 per cent or better, depending on the photometric band. Extensive comparisons with various literature sources show an overall ≃1 per cent agreement, which appears to be the current limit in the accuracy of flux calibrations across various samples and techniques in the literature. The Gaia photometric precision is presently of the order of 0.1 per cent or better, thus various ideas for the improvement of photometric calibration accuracy are discussed.